Teachers’ Gratification in Blended Teaching Modality in Tarlac National High School - Tan, Louise Angela (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between institutional support and teachers’ gratification in blended learning among Senior High School teachers at Tarlac National High School. Anchored on Maslow’s Hierarchy of Needs Theory, the study explored how trainings, equipment, facilities, and learning materials influenced teachers’ physiological, safety, belongingness, esteem, and self-actualization needs in blended teaching environments. The study employed a quantitative descriptive research design and utilized a researcher-made questionnaire validated by experts and tested for reliability using Cronbach’s Alpha. The respondents were Senior High School teachers from different academic and technical-vocational strands selected through total population sampling. Data were analyzed using frequency distribution, percentage, weighted mean, and ranking techniques. The findings revealed that the school support system in blended learning was generally rated as “Good,” indicating that trainings, equipment, facilities, and learning materials moderately supported teaching effectiveness. Teachers also reported “High Gratification” across Maslow’s hierarchy of needs, particularly in collegial support, professional recognition, instructional innovation, and opportunities for growth. However, challenges related to workload fatigue, limited technical support response, accessibility of resources, and concerns regarding job security remained evident. Based on the findings, the study proposed institutional interventions focusing on workload management, technical assistance, professional recognition, wellness initiatives, collaborative practices, and continuous professional development to improve teacher well-being and effectiveness in blended learning. The study supports SDG 4: Quality Education through the promotion of effective blended teaching and SDG 8: Decent Work and Economic Growth by emphasizing teacher well-being, professional development, and supportive working conditions. It also contributes to educational, institutional, technological, and socio-economic sustainability by strengthening teacher support systems and promoting sustainable blended learning practices in public secondary education.
Keywords: Blended Learning; Institutional Support; Maslow’s Hierarchy of Needs; Professional Development; Teacher Gratification; Teacher Well-Being; Trainings